Combustion performance and pollutant emissions analysis of a diesel engine fueled with biodiesel and its blend with 2-methylfuran. (1st February 2019) - Xiao, Helin; Yang, Xiaolong; Hou, Beibei; Wang, Ru; Xue, Qi; Ju, Hongling
Highlights: BM30 leads to deterioration of combustion at low engine load, while emits considerable emissions. Both regulated emissions and Unregulated emissions from biodiesel-MF blends were studied. The biodiesel-MF blends reduced the acetaldehyde and benzene emissions. Abstract: 2-Methylfuran (MF) is a promising and attractive alternative fuel with its improved production technology, but MF is rarely applied into compression ignition engines. Here the impacts of fuel characteristics and loads on burning and emissions were investigated in a four-cylinder direct-injection compression ignition engine fueled with biodiesel and its mixtures with MF. The experimental conditions were load at 0.13–1.13 MPa brake mean effective pressure (BMEP) and speed at 1800 rpm. At 0.13 MPa BMEP, with the rising MF mass fraction, the largest values of heat release rate and cylinder pressure both declined, but both increased at 0.63 and 0.88 MPa BMEP. Biodiesel-MF blends were featured with shorter burning duration and longer ignition delay at medium and high loads. Both regulated and unregulated emissions were measured. Less HC and CO and more NOx were emitted, while the soot emissions were constantly low with the increasing MF mass fraction. Unregulated emissions of 1, 3-butadiene, benzene and acetaldehyde decreased with the increasing MF mass fraction at both modest and high loads. With further engine loading, less benzene and acetaldehyde were emitted, while 1, 3-butadiene emissions first dropped and then rose. The biodiesel blended with low mass fraction of MF outperformed pure biodiesel in terms of combustion and emissions except for BM30.